Study Of Quality of Life in Antenatal Women Diagnosed with Gdm - Komal, Komal; Sharon, Minthami; Washington, Jasmine Kavitha (Journal of Neonatal Surgery, 2025)
Background: Gestational Diabetes Mellitus (GDM) is a common pregnancy complication that can significantly affect a woman’s physical and psychological well-being. Despite its medical implications, less attention has been given to the impact of GDM on the overall quality of life (QoL) during pregnancy. Objective: This study aims to assess the quality of life in women with GDM, focusing on physical, emotional, and social health, and to identify factors influencing their QoL. Methods: A cross-sectional study was conducted with 120 women diagnosed with GDM during pregnancy. Participants completed validated QoL questionnaires measuring physical health, emotional well-being, and social functioning. Data analysis explored the relationship between glycemic control, sociodemographic factors, and QoL outcomes. Results: Women with GDM reported lower QoL scores compared to the general pregnant population, particularly in emotional and physical domains. Poor glycemic control and higher levels of emotional distress were linked to reduced QoL. Higher family support and better adherence to medical recommendations positively impacted QoL scores. Conclusion: GDM significantly diminishes the quality of life, especially in emotional and physical aspects. A holistic approach, addressing both medical and psychological needs, is crucial for improving the overall well-being of women with GDM during pregnancy.